JNK and Autophagy Independently Contributed to Cytotoxicity of Arsenite combined With Tetrandrine via Modulating Cell Cycle Progression in Human Breast Cancer Cells - Yu, Bowen; Yuan, Bo; Li, JingZhe; Kiyomi, Anna; Kikuchi, Hidetomo; Hayashi, Hideki; Hu, Xiaomei; Okazaki, Mari; Sugiura, Munetoshi; Hirano, Toshihiko; Fan, Yingyi; Pei, Xiaohua; et al. (Frontiers in Pharmacology, 2020)
The need for novel therapeutic strategies for breast cancer remains paramount given the sustained development of drug resistance, tumor recurrence and metastasis. Trivalent arsenic derivatives (arsenite, AsIII) with remarkable clinical efficacy in acute promyelocytic leukemia has been demonstrated to exhibit inhibitory effect against breast cancer cells. We recently demonstrated that AsIII plus tetrandrine (Tetra), a Chinese plant-derived alkaloid, exerted potent antitumor activity against human breast cancer cells, however, the underlying mechanisms for its action have not yet been fully elucidated. In order to provide fundamental insights for understanding the action of AsIII plus Tetra, the effects of the combined regimen on two breast cancer cell lines T47D and MDA-MB-231 were evaluated. Although synergistic cytotoxic effects of AsIII and Tetra were observed in both cells, MDA-MB-231 cells were markedly more susceptible than T47D cells. Besides the induction of apoptotic/necrotic cell death, S-phase arrest and autophagic cell death were also observed in MDA-MB-231 cells. Exposure of MDA-MB-231 cells to AsIII and Tetra caused the activation of MAPKs. Inhibition of JNK by SP600125, a potent JNK inhibitor, significantly rescued MDA-MB-231 cells from the cytotoxicity of AsIII plus Tetra, however, similar cell viability restoration was not caused by p38 and ERK inhibitors. The addition of either autophagy inhibitors (3-methyladenine or wortmannin) or SP600125 corrected the combined regimen-triggered S-phase arrest, accompanied by an increase and a decrease of cell population in G2/M and G0/G1 phase respectively, whereas had little effect on the apoptosis/necrosis induction in MDA-MB-231 cells. Surprisingly, SP600125NC, a negative control for SP600125, significantly strengthened S-phase arrest and the cytotoxicity induced by the combined regimen. Inhibition of JNK by SP600125 did not alter autophagy induction. In conclusion, the cytotoxicity of the combined regimen of AsIII and Tetra were attributed to the induction of S-phase arrest, apoptotic/necrotic and autophagic cell death. The enhanced cytotoxicity of the two drugs by SP600125NC might be explained by its capability to strengthen S-phase arrest. JNK and autophagy independently contributed to the cytotoxicity via modulating cell cycle progression. Our results provide fundamental insights for the development of AsIII in combination with Tetra for patients with different types of breast cancer.